2017
DOI: 10.1007/s11357-017-9961-2
|View full text |Cite
|
Sign up to set email alerts
|

The phospholipid composition of the human entorhinal cortex remains relatively stable over 80 years of adult aging

Abstract: Membrane lipid composition is altered in the brain during the pathogenesis of several age-related neurodegenerative diseases, including Alzheimer's disease. The entorhinal cortex is one of the first regions of the brain to display the neuropathology typical of Alzheimer's disease, yet little is known about the changes that occur in membrane lipids within this brain region during normal aging (i.e., in the absence of dementia). In the present study, the phospholipid composition of mitochondrial and microsomal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
(54 reference statements)
2
28
0
Order By: Relevance
“…Funding information This work was supported by the National Institutes of Health (NIH) Grants R01-AT-006526, R01-AG047879, R01-AG038747, and R01-NS056218, the Geroscience Training Program in Oklahoma (NIH Grant T32-AG-052363), the Oklahoma Nathan Shock Center (NIH Grant 3-P30-AG050911-02S1), the Oklahoma Shared Clinical and Translational Resources (NIH Grant U54-GM-104938), the Oklahoma Center for the Advancement of Science and Technology (HR17-070), the College of Medicine Alumni Association, the Presbyterian Health Foundation, and the EU-funded grant EFOP-3.6.1-16-2016-00008. The paper was published as part of the BTranslational Geroscience^initiative of the Journal of the American Aging Association (Ashpole et al 2017;Bennis et al 2017;Callisaya et al 2017;Csiszar et al 2017;Deepa et al 2017;Grimmig et al 2017;Hancock et al 2017;Kane et al 2017;Kim et al 2017;Konopka et al 2017;Liu et al 2017;Meschiari et al 2017;Perrott et al 2017;Podlutsky et al 2017;Shobin et al 2017;Sierra and Kohanski 2017;Tarantini et al 2017a;Tarantini et al 2017b;Tenk et al 2017;Tucsek et al 2017;Ungvari et al 2017a, b ;Urfer et al 2017a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Funding information This work was supported by the National Institutes of Health (NIH) Grants R01-AT-006526, R01-AG047879, R01-AG038747, and R01-NS056218, the Geroscience Training Program in Oklahoma (NIH Grant T32-AG-052363), the Oklahoma Nathan Shock Center (NIH Grant 3-P30-AG050911-02S1), the Oklahoma Shared Clinical and Translational Resources (NIH Grant U54-GM-104938), the Oklahoma Center for the Advancement of Science and Technology (HR17-070), the College of Medicine Alumni Association, the Presbyterian Health Foundation, and the EU-funded grant EFOP-3.6.1-16-2016-00008. The paper was published as part of the BTranslational Geroscience^initiative of the Journal of the American Aging Association (Ashpole et al 2017;Bennis et al 2017;Callisaya et al 2017;Csiszar et al 2017;Deepa et al 2017;Grimmig et al 2017;Hancock et al 2017;Kane et al 2017;Kim et al 2017;Konopka et al 2017;Liu et al 2017;Meschiari et al 2017;Perrott et al 2017;Podlutsky et al 2017;Shobin et al 2017;Sierra and Kohanski 2017;Tarantini et al 2017a;Tarantini et al 2017b;Tenk et al 2017;Tucsek et al 2017;Ungvari et al 2017a, b ;Urfer et al 2017a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension in the elderly substantially increases the risk of Alzheimer's disease (AD); however, the underlying mechanisms are not completely understood (Forette et al 1998;Launer et al 2000;Israeli-Korn et al 2010;Guo et al 2001;Marr and Hafez 2014;Petrovitch et al 2000;van Dijk et al 2004;Joas et al 2012). In this review (published as part of the BTranslational Geroscience^initiative of the journal (Callisaya et al 2017;Kane et al 2017;Kim et al 2017;Liu et al 2017;Meschiari et al 2017;Perrott et al 2017;Shobin et al 2017;Ashpole et al 2017;Bennis et al 2017;Deepa et al 2017;Grimmig et al 2017;Hancock et al 2017;Konopka et al 2017;Podlutsky et al 2017;Sierra and Kohanski 2017;Tenk et al 2017;Ungvari et al 2017a;Urfer et al 2017a, b)), the effects of hypertension on structural and functional integrity of the cerebral microcirculation are considered, with a primary focus on cellular and molecular mechanisms involved in microvascular damage (capillary rarefaction, BBB disruption), neurovascular uncoupling, and the genesis of cerebral microhemorrhages and their potential role in exacerbation of cognitive decline associated with AD.…”
Section: Introductionmentioning
confidence: 99%
“…found that they were relatively unchanged during aging with only a 5-10% decrease in the oldest age group. A more recent study conducted by Hancock et al119 reported that PL content in the entorhinal cortex of older individuals is relatively stable during aging, but there is an increase in mitochondrial phosphatidylcholine (PC) and a decrease in mitochondrial phosphatidylethanolamine (PE). The same group reported that age is associated with an recent study used positron emission tomography to assess the incorporation of DHA from plasma to the brain using carbon-11 ([1-C 11 ])-DHA in apolipoprotein E epsilon allele (APOE4) carriers versus noncarriers .…”
mentioning
confidence: 99%